PENGARUH EXPANDED MARKETING MIX TERHADAP KEPUTUSAN BERKUNJUNG (Survei pada Wisatawan Nusantara yang Berkunjung ke Museum Sonobudoyo Yogyakarta) - Mardhatillah, Merliyani; Mulyadi, Hari; Hidayat, Marceilla (THE Journal : Tourism and Hospitality Essentials Journal, 2013)
Indonesia is an archipelagic state which are rich in natural wealth as flora and fauna and cultural variety that is a potential tourist destinations capable of interesting motivation tourists to perform the activities in Indonesia, and especially in Daerah Istimewa Yogyakarta. Yogyakarta city is the big cultural area in Indonesia that is a potential in terms of development cultural tour through the museum. But now a lot of people remain to regard that museum is just the place for keeping and maintaining historic and cultural fosils. The low appreciation of the society can be seem from the data of visitors attendance Museum Sonobudoyo Yogyakarta which shows a low number from years 2009 – 2010. Museum Sonobudoyo Yogyakarta conduct various attempts to increase the visits. One of the ways is through expanded marketing mix, which consists is people, physical evidence, and process. Expanded marketing mix in Museum Sonobudoyo Yogyakarta is expected to help increase tourist visits and for society awareness about cultural which has existed since long ago by the presence of museum. The independent variable (X) is expanded marketing mix which consists of three dimensions which are People, Physical evidence, and Process. The dependent variable (Y), namely the decision to visit. The type of the study is descriptive and verificative, and the method used was survey systematic random sampling technique, so it obtains 90 respondents of samples. Techniques of data analysis and hypothesis test used was multiple regression. Based on the research hypothesis, expanded marketing mix has a significant influence amounted to 48,5% towards visiting decision.